2015
DOI: 10.1111/bph.13011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of muscarinic receptor subtypes involved in catecholamine secretion in adrenal medullary chromaffin cells by genetic deletion

Abstract: BACKGROUND AND PURPOSEActivation of muscarinic receptors results in catecholamine secretion in adrenal chromaffin cells in many mammals, and muscarinic receptors partly mediate synaptic transmission from the splanchnic nerve, at least in guinea pigs. To elucidate the physiological functions of muscarinic receptors in chromaffin cells, it is necessary to identify the muscarinic receptor subtypes involved in excitation. EXPERIMENTAL APPROACHTo identify muscarinic receptors, pharmacological tools and strains of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…We examined the effect of mAChR activation on neurite growth using carbachol, which activates M1, M4, and M5 mAChRs endogenously expressed in PC12 cells (Berkeley and Levey ; Harada et al . ). Previous studies have shown that the Gαi coupled M4 mAChRs dominates in PC12 cells (Berkeley and Levey ).…”
Section: Discussionmentioning
confidence: 97%
“…We examined the effect of mAChR activation on neurite growth using carbachol, which activates M1, M4, and M5 mAChRs endogenously expressed in PC12 cells (Berkeley and Levey ; Harada et al . ). Previous studies have shown that the Gαi coupled M4 mAChRs dominates in PC12 cells (Berkeley and Levey ).…”
Section: Discussionmentioning
confidence: 97%
“…Of particular interest in CC biology is the potential role of muscarinic receptors, whose activation causes prolonged membrane depolarizations, increased cell firing and sustained catecholamines release [4, 21]. The action is mediated by the M1 muscarinic receptor [132] and proceeds through the inhibition of TASK1-like channels [130]. As muscarine activates the PKC pathway in RCCs [4, 133], it is likely that Nav channels may undergo the well-known PKC-dependent down-regulation mediated by muscarinic receptors [134].…”
Section: Tonic Versus Burst Firing In Chromaffin Cells: a “Neuron-likmentioning
confidence: 99%
“…; Harada et al . ). Briefly, rats were killed by cervical dislocation and the adrenal glands were taken out.…”
Section: Methodsmentioning
confidence: 97%
“…This muscarinic excitation in mouse AM cells was abolished by the genetic ablation of M 1 receptor (M 1 R) (Harada et al . ), and the muscarinic inhibition of TASK1 channels in rat and mouse AM cells was suppressed by MT7 (Harada et al . ), a specific M 1 R antagonist (Servent & Fruchart‐Gailard, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation